The Dale Carnegie leadership mastery course [ how to challenge yourself and others to greatness (Nightingale-Conant, 2000)
A course in 21st-century leadership designed to help move your career onto the fast track, at the same time sharpening decision-making, teaching effective response in a crisis and how to reduce anxiety under pressure. The skills in this package can also improve relationships at work and at home